Eosinophilic density in graft biopsies positive for rejection and blood eosinophil count can predict development of post‐transplant digestive tract eosinophilia. (24th February 2016) - Bush, Jonathan W.; Mohammad, Saeed; Melin‐Aldana, Hector; Kagalwalla, Amir F.; Arva, Nicoleta C.
Abstract: EGID is a known post‐transplant complication. Its etiology has been related to antirejection medication, but other factors may also play a role as only few transplant recipients develop EGID despite standardized treatment. This study aimed to determine whether EGID is associated with rejection events and with a specific phenotype of the rejection‐positive graft biopsies in children with solid organ transplant. All patients with liver, heart, and kidney transplant followed at our institution were included in the study. Digestive tract eosinophilia was more common in heart and liver recipients and was a rare event after renal transplantation. Subjects with EGID had higher incidence of rejection and elevated peripheral blood AEC. The first rejection event and high AEC values preceded EGID diagnosis in the majority of patients. Histologically, the initial rejection‐positive graft biopsy revealed accentuated eosinophilia in EGID patients compared with non‐EGID cohort, which correlated with higher blood eosinophil counts at the time of first rejection episode. Prominent graft tissue and peripheral blood eosinophilia prior to EGID diagnosis suggests a predisposition for eosinophil activation in patients with post‐transplant digestive eosinophilic disorder. These parameters can be used as markers for subsequent development of EGID.